Mapping Knowledge Trends in Regenerative Entrepreneurship - Judijanto, Loso; Wijayanti, Indah Oktari (The Es Economics and Entrepreneurship, 2025)
Regenerative entrepreneurship has emerged as a transformative paradigm that extends sustainability-oriented entrepreneurship by emphasizing the restoration, renewal, and enhancement of socio-ecological systems while creating economic value. Despite growing scholarly attention, research in this field remains fragmented across disciplines and lacks a systematic understanding of its intellectual structure and thematic evolution. This study aims to map knowledge trends in regenerative entrepreneurship through a comprehensive bibliometric analysis of publications indexed in the Scopus database. Using VOSviewer, the study applies network visualization, overlay visualization, density analysis, citation analysis, and collaboration mapping to examine thematic clusters, temporal dynamics, influential contributions, and patterns of scholarly collaboration. The findings reveal that regenerative entrepreneurship has evolved from foundations in classical entrepreneurship, economics, and organizational studies toward sustainability-oriented frameworks and, more recently, regenerative and systems-based perspectives. Three dominant thematic clusters are identified: institutional–economic entrepreneurship, regenerative innovation and place-based entrepreneurship, and sustainability-driven business model transformation. The results also indicate a concentration of research within specific countries and institutions, alongside emerging opportunities for broader international and interdisciplinary collaboration. Overall, this study provides a structured overview of the intellectual landscape of regenerative entrepreneurship, identifies key research gaps, and offers a foundation for future theoretical development and practical application in advancing regenerative economic systems.